2018
DOI: 10.1093/mnras/sty661
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stellar populations in Magellanic Cloud clusters – VI. A survey of multiple sequences and Be stars in young clusters

Abstract: The split main sequences (MSs) and extended MS turnoffs (eMSTOs) detected in a few young clusters have demonstrated that these stellar systems host multiple populations differing in a number of properties such as rotation and, possibly, age.We analyze Hubble Space Telescope photometry for thirteen clusters with ages between ∼40 and ∼1000 Myrs and of different masses. Our goal is to investigate for the first time the occurrence of multiple populations in a large sample of young clusters.We find that all the clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
184
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(207 citation statements)
references
References 67 publications
(111 reference statements)
19
184
3
Order By: Relevance
“…We have compared our CMD, which includes also the core He-burning loop, with isochrones of rotating models from the Geneva stellar models database 4 (Georgy et al 2014), provided by the SYCLIST code. We took into account the work done by Milone et al (2018), in which they show the presence of two families of stars in NGC 330, the bluest formed by non-rotating stars with an age compatible with 32 Myr (in agreement with our results), the reddest by rotating stars with angular velocity ω = 0.9ω c and age around 40 Myr, representing 40-55% of MS stars. As shown in Fig.…”
Section: Effect Of Stellar Rotationsupporting
confidence: 79%
“…We have compared our CMD, which includes also the core He-burning loop, with isochrones of rotating models from the Geneva stellar models database 4 (Georgy et al 2014), provided by the SYCLIST code. We took into account the work done by Milone et al (2018), in which they show the presence of two families of stars in NGC 330, the bluest formed by non-rotating stars with an age compatible with 32 Myr (in agreement with our results), the reddest by rotating stars with angular velocity ω = 0.9ω c and age around 40 Myr, representing 40-55% of MS stars. As shown in Fig.…”
Section: Effect Of Stellar Rotationsupporting
confidence: 79%
“…7 show that most of the observed Hα emitters are redder than the ordinary main sequence stars. This segregation is not a unique feature to NGC 330, with many LMC and SMC clusters exhibiting the same trait (Milone et al 2018). Telting et al (1998) have suggested through observations of Be stars whose spectra show rapid switching between containing emission lines and not, that the decretion disc can contribute up to 40% of a Be star's flux.…”
Section: Fast Rotators In the Colour-magnitude Diagrammentioning
confidence: 96%
“…To compare the models with observations of the SMC open cluster NCG 330 (Milone et al 2018) in the colour-magnitude diagram, the bolometric luminosities and effective temperature are converted to absolute magnitudes in the Hubble Space Telescope Wide-Field Camera 3 filters F814W and F336W by interpolating tables based on synthetic stellar spectra (Girardi et al 2002). The values of distance modulus and reddening adopted are (m − M) = 18.92 and E(B − V) = 0.06 respectively.…”
Section: Population Synthesismentioning
confidence: 99%
“…Correspondingly uncertain is the number of predicted OB+BH binaries. However, Wang et al (2020) have shown that the distribution of the sizable Be population of NGC 330 (Milone et al 2018) in the colour-magnitude diagram is well reproduced by detailed binary evolution models. In order to explain their number, however, the condition for stable mass transfer would have to be relaxed such that merging is prevented in more systems.…”
Section: Mass Transfer Efficiencymentioning
confidence: 99%